Effects of longitudinal optical phonon lifetimes on hot-carrier solar cells: a theoretical study. (12th September 2018) - Tsai, Chin-Yi
Abstract: Theoretical models and explicit formulas with the decay processes of optical phonons are presented for calculating intraband carrier energy relaxation rates. They are incorporated into the Ross-Nozik model for hot-carrier solar cells. Effects of LO phonon lifetimes on hot-carrier solar cells are investigated. The results demonstrate the potential of phononic engineering for producing optical-absorber materials with prolonged LO phonon lifetimes and slowed intraband carrier energy relaxation. They also suggest that using such materials can potentially provide a direct method of realizing hot-carrier solar cells.